First record of Matsubaraea fusiformis (Perciformes: Percophidae) in the waters of Western Taiwan: A taxonomic description - Wang, Yi-Chen; Mao, Yi-Chen; Lien, Yu-Yi (Zootaxa, 2024)
Herein, we present a new record of Matsubaraea fusiformis in western Taiwan waters; the discovery was based on its morphological characters. Five M. fusiformis samples were collected (August 2022) from the offshore waters (depth: 35.3–49.6 m) of Changhua County, western Taiwan, by using commercial bottom trawlers. A total of 5 genera and 10 species of the family Percophidae have been found in the waters of southwestern and northeastern Taiwan, primarily in the sandy deep-sea regions. This paper presents the first record of M. fusiformis in Taiwan. The findings also reveal that M. fusiformis is predominantly found in shallow waters.